Financial Protection Against Natural Disasters : An Operational Framework for Disaster Risk Financing and Insurance - World Bank Group (Washington, DC, 2015)
The primary objective of this report is to take stock of the global progress on financial protection against natural disasters over the last decade and bring together the latest thinking on disaster risk financing and insurance. Disaster risk financing and insurance helps minimize the cost and optimize the timing of meeting post-disaster funding needs without compromising development goals, fiscal stability, or wellbeing. Financial protection requires strong leadership by a country's ministry of finance. Disaster risk financing and insurance brings together disaster risk management, fiscal risk and budget management, public finance, private sector development, and social protection. While simple measures can quickly support improved financial protection, more complex financial solutions and institutional change require technical expertise and political will.